Numerical modeling of land subsidence induced by groundwater extraction considering unsaturated effects and using element-free Galerkin (EFG) method - A. Tourei; A. Pak; M. A. Iranmanesh (مهندسی عمران شریف)
This study aims to provide a coupled flow-deformation model for simulating land subsidence associated with groundwater extraction in aquifers. For this simulation, we have adopted the element-free Galerkin (EFG) method and considered the unsaturated effects in the aquifers based on the aquifer's hydrologic and geotechnical characteristics. This model gives us a better understanding of the aquifer's hydrogeological characteristics, enabling us to forecast changes in the hydraulic head and land subsidence. To ensure the credibility of our model and to verify the code, we modeled unsaturated hydromechanical benchmark problems. Then, using the EFG method as a numerical tool, we modeled an isotropic aquifer to investigate the effects of groundwater pumping on land subsidence and hydraulic changes in the aquifer. To ascertain the reliability of the modeling, we compared the results obtained from the EFG method with those from the Finite Element Method (FEM). The comparative analysis of EFG and FEM models demonstrates discrepancies of 5.51% in land subsidence and 13.35% in hydraulic head reduction, which are satisfying. The land subsidence and hydraulic head profiles demonstrate that the EFG method is capable of land subsidence simulation caused by water pumping. Furthermore, our findings highlight the nonlinear correlation between groundwater extraction and the subsequent decrease in hydraulic head and land subsidence augmentation. Finally, we conducted a parametric study to better understand the effect of various characteristics of aquifers and observe the effect of the aquifer's parameters, such as hydraulic conductivity, elastic modulus, and Poisson's ratio. We investigated the effect of each parameter on land subsidence increase and hydraulic head decline. The results show that elastic modulus and Poisson's ratio have the most significant effect on land subsidence. Although hydraulic conductivity controls the hydraulic decrement and land subsidence increase time, it slightly affects the ultimate hydraulic head and land subsidence at the steady-state stage. These results highlight the importance of in-situ measurement of elastic modulus and Poisson's ratio paraeters with acceptable accuracy for groundwater extraction projects, as these parameters play a significant role in the feasibility studies.